Penerapan model pembelajaran berdasarkan matematika untuk meningkatkan kemampuan berpikir kreatif matematis siswa kelas X SMA Negeri 19 Medan T.A. 2017/2018 - Tambunan, Dian Rizky Utami (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The aims of this study were to (1) improve the students’ mathematics creative thinking ability, (2) analyze the students’ mathematic study completeness of students in X MIA 1, (3) find out the respons of the students in X MIA by appliying mathematic problem based learning. The type of research used in this study was Classroom Action Research. The subject of this study was the all of the students in X MIA 1 SMA Negeri 19 Medan 2017/2018 study year that amounts to 32 people. The object of this study was the students’ mathematics creative thinking ability. This study done in 2 cycles contained of two times of meetings each cycle. At the end of each cycle, given two questions of mathematics creative thinking ability test. Based on the datas’ analysis of the test after the first action extending obtained that 15 students (46,87%) of 32 students already achieved the study completeness (≥70). After the second action, obtained that 27 students (84,37%) of 32 students achieved the study completeness. Occur a rising classical completeness percentage in amount of 37,5%. Based on the criteria of classical completeness, this percentage already fulfilled. Based on the research’s result, concluded that there’s a rising of mathematics creative thinking ability in X MIA 1 SMA Negeri 19 Medan so the application of problem based learning model could be used as one of the alternative to increase mathematics creative thinking ability.